Reconstruction of Conditional Death Penalty Norms In the Perspective of Renewing Indonesian Criminal Law - Joko Cahyono; Faisal Santiago (Publikasiku, 2023)
Penal reform is something that must be done as a form of adjustment to applicable law with changes in values, times, technology, national and international insights. Death penalty in Indonesia also needs to be updated to adjust these developments, especially in the adjustment of the values adopted by the Indonesian people. This study aims to determine the policy on conditional death penalty formulation in the law currently in force in Indonesia, and analyze the policy formulation of the ideals of conditional death penalty in Indonesia. This research uses a qualitative method with a normative approach. This research results in the fact that the law in Indonesia has not yet regulated the conditional death sentence, so there is still a conflict between those who want to abolish capital punishment and those who want to continue implementing capital punishment. Conditional death penalty is needed as a middle ground between the two groups. Conditional death penalty is also needed as an evaluatif process for prisoners in serving their sentences and respecting human rights in accordance with national and international perspectives